DETERMINANTS OF FACTORS INFLUENCING THE PURCHASE DECISIONS OF CHATIME BEVERAGES BY GENERATION Z IN NORTH SUMATRA: THE ROLE OF SELF-CONTROL AS A MODERATING VARIABLE - Siagian, Salsabilla; Tarigan, Azhari Akmal; Lubis, Fauzi Arif (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to analyze the influence of e-money, promotions, and lifestyle on the purchase decisions of Chatime beverages among Generation Z in North Sumatra, with self-control as a moderating variable. Data were collected through a survey of 100 Generation Z respondents who met the research criteria. The data analysis technique used was the Moderated Regression Analysis (MRA). Data processing was conducted using SPSS 25. The results indicate that e-money, promotions, and lifestyle significantly affect the purchase decisions of Chatime beverages among Generation Z in North Sumatra Medan. Furthermore, simultaneous analysis shows that e-money, promotions, and lifestyle collectively have a significant influence on purchase decisions. However, self-control does not have a significant impact on purchase decisions. Additionally, self-control does not significantly strengthen the relationship between e-money and lifestyle. Self-control significantly weakens the relationship between promotions and purchase decisions and significantly strengthens the relationship between lifestyle and purchase decisions.